Atherosclerosis: from lipid-lowering and anti-inflammatory therapies to targeting arterial retention of ApoB-containing lipoproteins - Araujo, Gala; Valencia, Leidy Marian; Martin-Ozimek, Agata; Soto, Yosdel; Proctor, Spencer D. (Frontiers in Immunology, 2025)
Atherosclerosis is a chronic inflammatory disease characterized by the accumulation of lipids, fibrous elements, and cellular debris in the blood vessels. The response-to-retention hypothesis, the leading theory on the pathogenesis of this cardiovascular disease, describes the initial event in atherosclerosis as when Apolipoprotein B-containing lipoproteins, including endogenous and dietary-derived lipoproteins, bind to the inner arterial wall, the tunica intima. The subsequent lipoprotein modifications trigger an immune response that promotes atherosclerotic plaque formation. Despite the prevalence of atherosclerosis globally, and its vascular nature, therapies directed to the artery wall are limited. Immunotherapies, most notably monoclonal antibodies (mAbs), are of special interest due to their high specificity, reliability and proven success in a variety of diseases. However, current mAbs for atherosclerosis tend to target disease risk factors, notably inflammation and circulating lipoprotein levels, rather than address the root cause of atherosclerosis. These treatments result in a phenomenon known as residual risk, defined by the occurrence of severe cardiovascular events, including myocardial infarction, during treatment. Per the “response to retention” hypothesis, a plausible strategy for atherosclerosis would be blocking cholesterol retention per se at the arterial extracellular matrix level to complement lipid-lowering therapies. One such immunotherapy is the chP3R99 mAb, which can bind to pro-atherogenic proteoglycan sugar branches, thus competitively inhibiting lipid retention at these sites. The aim of this review is twofold: 1) To provide a summary of mAbs and other therapies used for atherosclerosis treatment, focusing on anti-inflammatory and lipid-lowering therapies, and 2) To review data on the structural characteristics, theory, and therapeutic effect of the chP3R99 mAb.